Structural transitions and energy use: a decomposition analysis of Portugal 1995–2010. Issue 2 (2nd April 2016) - Guevara, Zeus; Rodrigues, João F. D.
ABSTRACT: The Portuguese energy sector changed substantially during the period 1995–2010, with the introduction of natural gas and a larger renewable energy production. During the same period, the country also continued the shift to a service economy. By 2005, these two transitions led to a large increase in primary energy use (PEU), followed by a significant decline until 2010. The goal of this paper is to identify the main driving factors of changes in the Portuguese PEU through structural decomposition analysis. To do so we build a novel hybrid model with a detailed description of the energy sector in physical units, and a coarser description of the rest of the economy in monetary units. The results show that the main drivers were final demand (increasing PEU) and the direct energy intensity (decreasing PEU); while the energy and economic transitions also contributed to decrease PEU, although to a lesser extent.